2016
DOI: 10.1007/s00430-016-0456-z
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesviruses respiratory infections in patients with acute respiratory distress (ARDS)

Abstract: Acute respiratory distress syndrome (ARDS) is today a leading cause of hospitalization in intensive care unit (ICU). ARDS and pneumonia are closely related to critically ill patients; however, the etiologic agent is not always identified. The presence of human herpes simplex virus 1, human cytomegalovirus and Epstein-Barr virus in respiratory samples of critically ill patients is increasingly reported even without canonical immunosuppression. The main aim of this study was to better understand the significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 34 publications
(45 reference statements)
2
27
1
Order By: Relevance
“…Results of 1 study included codetection with EBV and respiratory viruses [9]; another reported codetection with respiratory viruses, with codetection rates ranging from 2% to 8% [6]. Results of prior studies suggest that infection with influenza and other respiratory viruses might reactivate herpes family viruses [31, 32]. In our study, patients with codetections did not report higher frequency of complications, hospitalizations, or underlying medical conditions compared with patients having samples with single virus detection.…”
Section: Discussionmentioning
confidence: 54%
“…Results of 1 study included codetection with EBV and respiratory viruses [9]; another reported codetection with respiratory viruses, with codetection rates ranging from 2% to 8% [6]. Results of prior studies suggest that infection with influenza and other respiratory viruses might reactivate herpes family viruses [31, 32]. In our study, patients with codetections did not report higher frequency of complications, hospitalizations, or underlying medical conditions compared with patients having samples with single virus detection.…”
Section: Discussionmentioning
confidence: 54%
“…The AUC was 0.369 (95% CI 0.292 to 0.446) for age, 0.425 (95% CI 0.345 to 0.505) for the APACHE II score, and 0.355 (95% CI 0.278 to 0.433) for the SOFA score (not shown) During the past decade, there have been a few investigations addressing the potential function of the lymphocyte/neutrophil ratio, which remains a useful test for the diagnosis of tuberculous pleuritis [19] and acts as an early biomarker for predicting acute rejection after heart transplantation [20]. Previous studies have focused on the poor prognosis of patients with severe lymphopenia from the first day of ICU admission [21]. In our study, peripheral blood lymphopenia was very common in ARDS patients without typical underlying diseases, causing immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on early T-cell lymphopenia, which has been widely attributed to viral infection, and patients with a poor prognosis had severe lymphopenia from the first day of ICU admission [29]. In our study, it was found that peripheral blood lymphopenia was very common in ARDS patients without typical underlying diseases causing immunosuppression.…”
Section: Discussionmentioning
confidence: 51%
“…In particular, a clear reduction in the number of circulating lymphocytes was evident in this group when compared to the group of patients discharged from the intensive care unit (ICU). The reduction in lymphocytes involves all lymphocyte populations: T (CD3+), B (CD19+) and NK cells (CD3CD16/56+) [13]. A high neutrophil-to-lymphocyte ratio (NLR) was associated with poor outcomes in critically ill patients with ARDS [14,15].…”
mentioning
confidence: 99%